The Multifaceted Nature of Food and Nutrition Insecurity around the World and Foodservice Business - Raposo, António; Han, Heesup (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The international concept of food security is a situation where all people have physical, social, and economic access at all times to sufficient, safe, and nutritious food that meets their dietary needs and food preferences for an active and healthy life. All four parameters (availability, access, utilization, and stability) should therefore be measured to determine food security status.Taking into account these premises, this book aims to present original research articles and reviews concerning the following: Agriculture and food security; Agri-tourism and its potential to assist with food security; Business-science cooperation to advance food security; Competing demands and tradeoffs for land and water resources; Consumer behavior, nutritional security and food assistance programs; Food and health; Global and local analyses of food security and its drivers; Global governance and food security; Infectious and non-infectious diseases and food security; Reducing food loss and waste; Reducing risks to food production and distribution from climate change; Supply chains and food security; Technological breakthroughs to help feed the globe; Tourism food security relationship; Urbanization, food value chains, and the sustainable, secure sourcing of food; Food and service quality at food catering establishments; Consumer behavior at foodservice operations (restaurants, cafés, hotels).